Recherche Descriptive sur les Structures et les Concepts Sour-Jacents au Contenu du Programme d’Information Scolaire et Professionnelle - Limoges, Jacques (Canadian Journal of Counselling and Psychotherapy, 2012)
Educational and Occupational Information (EOI) is defined as the useful or necessary informations required to make a vocational choice. In Quebec, like in many countries, some educators are trained and specialized to communicate the EOI. In recent years, their techniques and methods have improved significantly, but in spite of pointed weaknesses (Fontaine, 1973), their content remains the same. However, a taxonomic study of this content reveals a hierarchic and integrative structure that, on the one hand, gives the content a time-proof quality required for meaningful integration, and on the other hand, reduces the content from items to principles, via concepts; each level representing a dimension of the school and career environment. The role of the"Informer" is to help the individual to interact with this environment.